STRUKTUR MODAL, UKURAN, DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN: PERAN TATA KELOLA SEBAGAI PEMODERASI - Nurrochmi, Eka Alfiyah; Rahmatika, Dien Noviany; Susetyo, Budi (Catholic University Musi Charitas, 2025)
Purpose: This study investigates the effects of capital structure, firm size, and financial performance on firm value, and examines the moderating role of institutional ownership in Indonesian conventional banks. Design/Methodology/Approach: A quantitative approach was applied using secondary data from 42 conventional banks listed on the Indonesia Stock Exchange (IDX) during 2020–2024, totaling 210 firm-year observations. The data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS version 25. Findings: Capital structure, firm size, and financial performance significantly affect firm value. Institutional ownership significantly moderates the effect of firm size on firm value with a negative direction, indicating that higher institutional control can weaken the size–value relationship. Practical Implications: Bank managers should balance debt and equity structures and maintain transparency with institutional investors to optimize firm value. Originality/Value: This study extends corporate governance research by integrating institutional ownership as a moderating variable in the firm value model within a regulated emerging-market banking sector.